2018
DOI: 10.1186/s13054-018-1985-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of a low ratio of visceral to subcutaneous adipose tissue depends on LDL clearance versus production in sepsis

Abstract: BackgroundPatients with sepsis with a high ratio of visceral adipose tissue (VAT) to subcutaneous adipose tissue (SAT) have increased mortality. Our goal was to investigate the mechanism of this effect, noting that low LDL levels are also associated with increased sepsis mortality. Accordingly we tested for association between VAT/SAT, low-density lipoprotein (LDL) levels, and mortality. Then we examined the effect of statin treatment, which decreases LDL production, and the effect of PCSK9 genotype, which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In this context, our results point to LDL as contributing to inflammation and with impaired scavenger capacity. It is noteworthy, however, that while reduced LDL production is related to a complicated prognosis, LDL clearance can improve survival [51].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, our results point to LDL as contributing to inflammation and with impaired scavenger capacity. It is noteworthy, however, that while reduced LDL production is related to a complicated prognosis, LDL clearance can improve survival [51].…”
Section: Discussionmentioning
confidence: 99%
“…Serum lipids have been proven to be closely related to sepsis progression. Several studies have shown that patients with sepsis have decreased plasma total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C), and subsequently, patients with low TC, HDL-C and LDL-C levels have higher death risk [6][7][8]. Additionally, patients with sepsis also have increased triglycerides (TG) and decreased lipoprotein(a) (Lp(a)) [9].…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor: T he network meta-analysis done by Ramadanov et al (1), published in a recent issue of Critical Care Medicine, suggests that in patients treated with targeted temperature management at 32-34°C after cardiac arrest, intravascular cooling is the most beneficial cooling method for neurologic outcome and survival, followed by surface cooling with temperature feedback. In their discussion, they noted several adverse events associated with intravascular cooling, including infection, hemorrhage, and catheter-related thrombosis-which can lead to pulmonary embolism (1). We would like to emphasize the importance and frequency of certain complications linked to intravascular cooling that the authors mentioned very briefly (1).…”
Section: Safety Concerns In Intravascular Cooling For Targeted Temper...mentioning
confidence: 99%